Distinct migratory pattern of naive and effector T cells through the blood-CSF barrier following Echovirus 30 infection - Wiatr, Marie; Stump-Guthier, Carolin; Uhlig, Stefanie; Weiß, Christel; Schwerk, Christian; Schroten, Horst; Tenenbaum, Tobias; Rudolph, Henriette (Journal of neuroinflammation, 2019)
Echovirus 30 (E-30) is one of the most frequently isolated pathogens in aseptic meningitis worldwide. To gain access to the central nervous system (CNS), E-30 and immune cells have to cross one of the two main barriers of the CNS, the epithelial blood-cerebrospinal fluid barrier (BCSFB) or the endothelial blood-brain barrier (BBB). In an in vitro model of the BCSFB, it has been shown that E-30 can infect human immortalized brain choroid plexus papilloma (HIBCPP) cells.